BS EN IEC 60404-17. Magnetic materials. Part 17. Methods of measurement of the magnetostriction characteristics of grain-oriented electrical steel strip and sheet by means of a single sheet tester and an optical sensor (6th November 2020) - British Standards Institution,
No abstract available